2022
DOI: 10.3389/fmicb.2022.994847
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Bacillus subtilis antagonize soil-borne fungal pathogens and suppress wilt complex disease in chickpea plants (Cicer arietinum L.)

Abstract: The present study aimed to identify potential endophytic bacteria antagonistic against three soil-borne fungal pathogens, Rhizoctonia solani, Sclerotium rolfsii, and Fusarium oxysporum f.sp. ciceri causing root rot, collar rot, and fungal wilt diseases in chickpea plants, respectively. A total of 255 bacterial endophytes were isolated from the leaves, stems, and roots of seven different crop plants (chickpea, tomato, wheat, berseem, mustard, potato, and green pea). The dual culture-based screening for antifung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Siderophores have a high affinity for Fe 3+ and are capable of binding Fe 3+ to form complexes, which helps Fe uptake by microorganisms, as well as being taken up by plants to increase iron content within the tissues and promote plant growth [ 41 ]. A study by Mageshwaran et al revealed that one of the factors that Bacillus subtilis TRO4 promotes in the growth of chickpea plants is the production of siderophores [ 42 ]. In line with previous reports, the ability of JK-25 to produce siderophores was verified in this study by the CAS blue agar plate method as one of the reasons for the ability to promote wheat growth.…”
Section: Discussionmentioning
confidence: 99%
“…Siderophores have a high affinity for Fe 3+ and are capable of binding Fe 3+ to form complexes, which helps Fe uptake by microorganisms, as well as being taken up by plants to increase iron content within the tissues and promote plant growth [ 41 ]. A study by Mageshwaran et al revealed that one of the factors that Bacillus subtilis TRO4 promotes in the growth of chickpea plants is the production of siderophores [ 42 ]. In line with previous reports, the ability of JK-25 to produce siderophores was verified in this study by the CAS blue agar plate method as one of the reasons for the ability to promote wheat growth.…”
Section: Discussionmentioning
confidence: 99%
“…Siderophores have a high affinity for Fe 3+ and are capable of binding Fe 3+ to form complexes, which make Fe easier for uptaking by microorganisms, as well as being taken up by plants to increase iron content within the tissues and promote plant growth [41]. A study by Mageshwaran et al revealed that one of the factors that Bacillus subtilis TRO4 promotes the growth of chickpea plants is the production of siderophores [42]. In line with previous reports, the ability of JK-25 to produce siderophores was verified in this study by the CAS blue agar plate method as one of the reasons for the ability to promote wheat growth.…”
Section: Discussionmentioning
confidence: 99%
“…It was established that the P. aeruginosa C10 strain has the highest bactericidal activity against pathogenic bacteria: Bacillus badius, B. mesentericus, B. mojavensis (Kadyrova et al, 2022). Mageshwaran et al (2022) investigated the antagonism of endophytic bacteria. 255 bacterial endophytes were isolated from the leaves, stems and roots of seven different cultivated plants (chickpea, tomato, wheat, bersem, mustard, potato and green peas).…”
Section: Discussionmentioning
confidence: 99%